A critical analysis on recovery process for Islamic banking facilities in Malaysia / Nurul Fatihah Mat Zaizait … [et al.] - Mat Zaizait, Nurul Fatihah; Md Saif, Nor Afiqah; Hashim, Norliayanaamirah; Mohamed, Siti Asilah (Faculty of Law, 2013)
This research study consists of all chapters on our research background, products and recovery process for Islamic banking facilities in Malaysia. The purpose of this study is to analyses whether the current practice of recovery process is in compliance with syariah principle or not. Then, we compare the procedures in recovery debt between conventional banking and Islamic banking. Moreover, this study is important in ensuring that all customers in banking transaction would be aware of their liability and the consequences in the event of default payment. This study also highlights the importance of public awareness in the matters relating to the Islamic banking facilities.